Brain Structural-Behavioral Correlates Underlying Grooved Pegboard Test Performance Across Lifespan. Issue 3 (4th July 2020) - Yao, Zai-Fu; Yang, Meng-Heng; Hsieh, Shulan
Abstract: This study aims to provide the first brain structural-behavioral correlates underlying age differences in Grooved Pegboard Test (GPT) performance after adjusting for gender, education, quality of life, mental health, and anthropometric variables. We report the data of 210 right-handed participants (20- to 80-year old), who underwent behavioral assessments including GPT, Trail Making Test, and stop-signal task. Magnetic resonance images were acquired to investigate the structural-behavioral correlates of age differences in GPT performance. Age differences in GPT performance were positively associated with visuomotor tracking performance and negatively associated with widespread brain structural measures, including white matter tracts (e.g., commissure, radiation, and association fibers) and gray matter regions in frontal and cingulate regions, parietal, and temporal lobes.